Origin and evolution of the Santiaguito lava dome complex, Guatemala - Scott, J (2013)
Subduction zone volcanoes are a major natural hazard, frequently endangering lives and livelihoods. The eruptive history of many subduction zone volcanoes includes the extrusion of blocky, silicic lava that forms domes or flows, but we do not yet understand what determines the duration of dome-forming behaviour, what path magma may take to the surface, or how these systems may change over time. This thesis presents an investigation of the Santiaguito complex of lava domes and flows in Guatemala, which has been erupting continuously since its inception in 1922. The Santiaguito lavas are predominantly dacitic to andesitic, with a gradual reduction in SiO2 content from ~66 wt% in the 1920s, to ~62 wt% in 2002. This is consistent with a ~15% decrease in the extent of fractional crystallization over that time. The compositions of plagioclase phenocryst cores indicate a diminished role for magma mixing after the 1940s. I model the Santiaguito system as progressively extracting magma from an extensive, chemically-stratified storage zone. Petrological data are consistent with a storage zone extending from ~25 to ~12 km depth, and magma storage temperatures of ~940 to ~980°C. Phenocryst-hosted apatites suggest melt in this storage zone contained 401 to 1199 ppm S, 600 to 1300 ppm F, and 4100 to 6200 ppm Cl. Ascending magma may pass slowly through a conduit bottleneck, or plug, at shallow depths; groundmass texture suggests that melt rigidifies at or near the base this plug. Pre-eruptive melt volatile concentrations suggest time-averaged fluxes of 40 to 263 Mg d-1 SO2, 32 to 145 Mg d-1 HF, and 247 to 708 Mg d-1 HCl, giving ratios of 0.6 to 0.8 HF/SO2, and 2.7 to 6.2 HCl/SO2. These results are consistent with the few direct measurements of SO2 at Santiaguito, and with measured halogen emissions from other silicic dome-forming systems.